The Influence Of E-Wom (Electronic Word Of Mouth), Sales Promotion And Brand Image On The Purchase Decision Of Scarlett Whitening Products On The Shopee Marketplace - Karsih; Liling Listyawati; Damajanti Sri Lestari; Priyanto (International Journal of Business and Quality Research, 2025)
The research was used to determine the relationship between e-WOM (Electronic Word Of Mouth), sales promotion, and brand image to consumer decisions in purchasing Scarlett Whitening products on the Shopee platform. The method in this study is quantitative carried out using survey techniques. The distribution of questionnaires to one hundred respondents who use Scarlett Whitening products through Shopee produced the data needed for data analysis, which was carried out through the stages of classical assumption tests that included multicollinearity, normality, and heteroscedasticity, data analysis was carried out using multiple linear regression. The results show that e-WOM, sales promotion, and brand image have a positive and significant influence on purchasing decisions, both separately and simultaneously. These three independent variables contributed 58.8% to the variation in purchasing decisions, based on the value of the determination coefficient (R2) which reached 0.588. Of all the factors studied, Purchasing decisions are most triggered by perceptions of brand image. This shows that the impression of the brand in the minds of consumers is the main trigger that drives purchase intent, even stronger than other factors such as digital communication strategies and strengthening brand image in making wise purchase decisions when shopping online. Companies should continue to strive to improve their brand reputation and maintain their e-WOM (Electronic Word Of Mouth) strategy as well as targeted promotions, which can be an additional trigger that encourages consumers to make a purchase decision.